Pencegahan Risiko Jatuh Pada Lansia Dengan Penyakit Degeneratif - Nurhayati Nurhayati; Eva Oktavidiati; Lussyefrida Yanti (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2023)
The risk of falling is an incident reported by the sufferer or family who saw the incident, which resulted in a person suddenly falling down, sitting on the floor or a lower place with or without loss of consciousness or injury. Based on an initial survey at the Posyandu Lansia Akbar (Elderly Center) in the working area of ​​the Puskesmas Jembatan Kecil (Community Health Center), it was found that some health problems which are still often experienced by the elderly are degenerative diseases such as hypertension, diabetes mellitus, and perceptual and sensory disorders that leads in decreasing balance, muscle strength and flexibility. These problems put elderly at high risk of falls. To reduce the risk of falls in the elderly, it is necessary to provide preventive, curative and collaborative health services in the form of health education and assistance with balance exercises. So the Community Service Team provides health education on preventing the risk of falls in the elderly.